2020
DOI: 10.3390/en13051184
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Lean Management as a Tool for Decrease of Energy Consumption and CO2 Emissions in the Fast Food Restaurant

Abstract: The manuscript presents the possibilities of using selected Lean Management tools at a fast food restaurant located at the international airport terminal in Poland. Observations in other points of the company lasting for five years, made possible fair proposals for improvement of selected elements of production and work organization. The research part presents the results of application of such tools as value stream mapping (VSM), Kaizen, and 5S. The Lean Management method, chosen after careful analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…From an operational perspective, Lean implements a set of shop floor tools and techniques that aim to reduce waste. These tools include work standardization, kaizen, setup time reduction, visual displays, and Kanban [15][16][17][18].…”
Section: Analysis Of the Literaturementioning
confidence: 99%
“…From an operational perspective, Lean implements a set of shop floor tools and techniques that aim to reduce waste. These tools include work standardization, kaizen, setup time reduction, visual displays, and Kanban [15][16][17][18].…”
Section: Analysis Of the Literaturementioning
confidence: 99%
“…We list comparisons among our new model and those existing systems to illustrate our contribution to the academic society (Table 1). Aiello et al [20] Avinadav [34] Avinadav and Arponen [13] Avinadav et al [14] Avinadav et al [18] Avinadav et al [27] Bhuiya et al [40] Chernonog [35] Chernonog andAvinadav [31] Chuang and Lin [21] De Giovanni [9] Demirag [28] Ganguly et al [41] Gładysz et al [7] Hanukov et al [32] Hanukov et al [36] Herbon [19] Hota et al [42] Khan et al [43] Kim et al [44] Krommyda et al [37] Lee et al [3] Leśniewski and Bartoszewicz [15] Lin et al [11] Ma [22] Malik and Sarkar [10] Mishra et al [45] Muriana [23] Muriana [25] Muriana [29] Muriana [38] Orynycz et al [8] Sarkar et al [1] Sharma et al [30] Taleizadeh et al [46] Yang et al [12] Zimpel-Leal and Lettice [4] Sarkar [47] Sarkar [48] Sepehri et al [49] This study Abbreviations for the first row: S1: Sustainable; B: Backordering; L: Lean management; S2: Supply chain; P1: Pricing; S3: Shelf-life; W: Waste management; P2: Perishable.…”
Section: A Literature Review Among Modelsmentioning
confidence: 99%
“…Rubio-Valdehita et al [5] and Górska-Warsewicz et al [6] examined retailing companies. Gładysz et al [7] and Orynycz et al [8] presented lean management. De Giovanni [9] and Malik, and Sarkar [10] developed supply chain philosophies.…”
Section: Introductionmentioning
confidence: 99%
“…organizations apply some principles of lean, but label it differently, making it difficult to attribute any successful practices to a specific lean management principle. Some articles adopted a comprehensive review of lean management approaches and reported details of applications of full-scale lean programs [42,[44][45][46][47][48][49]51,53,55,61,62]. Others addressed one or more specific tools [43,50,52,55,59,60], environmental issues [52,55,59,62] or proposed lean implementation and waste frameworks for HoReCa [54,59,60].…”
Section: Full-scale Lean Specific Tool Environmental Issuesmentioning
confidence: 99%
“…There is no single consistent topical stream in this category. Different authors reported a framework for measuring, monitoring, managing green practices and classifying waste in restaurants [59], contribution of lean tools (VSM, kaizen, and 5S) to increase work efficiency, decrease of cycle times and reducing energy consumption and CO 2 emissions while maintaining a high level of quality in restaurants [62].…”
Section: Full-scale Lean Specific Tool Environmental Issuesmentioning
confidence: 99%